2016
DOI: 10.3389/fpsyg.2015.01982
|View full text |Cite
|
Sign up to set email alerts
|

What can Written-Words Tell us About Lexical Retrieval in Speech Production?

Abstract: In recent decades, researchers have exploited semantic context effects in picture naming tasks in order to investigate the mechanisms involved in the retrieval of words from the mental lexicon. In the blocked naming paradigm, participants name target pictures that are either blocked or not blocked by semantic category. In the continuous naming task, participants name a sequence of target pictures that are drawn from multiple semantic categories. Semantic context effects in both tasks are a highly reliable phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 84 publications
1
15
0
Order By: Relevance
“…Blocked-cyclic and continuous naming tasks are used often interchangeably to draw inferences about the nature of semantic interference effects in naming and the processes that underlie speech production in general (Blocked Cyclic Naming: e.g., Belke, 2008, 2013; Damian & Als, 2005; de Zubicaray et al, 2014; Meinzer et al, 2016; Navarrete, Mahon, Lorenzoni, & Peressotti, 2016; Schnur et al, 2006, 2009; Continuous Naming: e.g., Belke, 2013; Canini et al, 2016; Howard et al, 2006; Navarrete et al, 2010; Ries et al, 2015; Rose & Abdel Rahman, 2016a, b; Schnur, 2014). While previous research has discussed the extent to which these two tasks may or may not reflect the same processes (Belke & Stielow, 2013), to our knowledge, this is the first study which provides a direct empirical comparison of semantic interference effects across these two tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocked-cyclic and continuous naming tasks are used often interchangeably to draw inferences about the nature of semantic interference effects in naming and the processes that underlie speech production in general (Blocked Cyclic Naming: e.g., Belke, 2008, 2013; Damian & Als, 2005; de Zubicaray et al, 2014; Meinzer et al, 2016; Navarrete, Mahon, Lorenzoni, & Peressotti, 2016; Schnur et al, 2006, 2009; Continuous Naming: e.g., Belke, 2013; Canini et al, 2016; Howard et al, 2006; Navarrete et al, 2010; Ries et al, 2015; Rose & Abdel Rahman, 2016a, b; Schnur, 2014). While previous research has discussed the extent to which these two tasks may or may not reflect the same processes (Belke & Stielow, 2013), to our knowledge, this is the first study which provides a direct empirical comparison of semantic interference effects across these two tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Both tasks elicit semantic interference whereby naming multiple items from the same semantic category slows production. Interference in both tasks generally responds similarly under different conditions, for example when items are semantically or associatively similar (e.g., Abdel Rahman & Melinger, 2007; Rose & Abdel Rahman, 2016a,b; Vigliocco, Vinson, Damian, & Levelt, 2002), items are interleaved with unrelated items or time (Damian & Als, 2005; Howard et al, 2006; Schnur et al 2006; Schnur, 2014), the stimulus modality varies (pictures vs. words; Belke, 2013; Damian et al, 2001; Navarrete et al, 2016) or when items are categorized instead of named (Belke, 2013; Damian et al, 2001). For these reasons, blocked cyclic and continuous naming are considered variations of the same paradigm (i.e., serial naming) and multiple researchers when discussing semantic interference effects in speech production attribute these effects to the basic process of learning independent of the task in which they are observed (e.g., blocked cyclic naming or continuous naming; Belke & Stielow, 2013; Breining, Nozari, & Rapp, 2016; Crowther & Martin, 2014; Damian & Als, 2005; Howard et al, 2006; Kleinman, Runnqvist, & Ferreira, 2015; Llorens, Dubarry, Trebuchon, Chauvel, Alario & Liegeois-Chauvel, 2016; Navarrete et al, 2016; Navarrete et al, 2014; Oppenheim et al 2010; Rose & Abdel-Rahman, 2016a,b; Schnur et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Vitkovitch and colleagues found that word naming interfered with subsequent naming of semantically related pictures (Vitkovitch & Cooper, 2012;Vitkovitch, Cooper-Pye, & Ali, 2010). In contrast, Navarrete and colleagues found that picture naming interfered with subsequent printed word naming, but not vice versa (Navarrete et al, 2010;Navarrete, Mahon, Lorenzoni, & Peressotti, 2016; see also Belke, 2013). Studying the role of the presence of a partner in a shared naming task, Kuhlen and Abdel Rahman (subm.…”
mentioning
confidence: 99%
“…In fact, Damian et al (2001) reported facilitation in this task, while others have reported no significant effect of semantic blocking (e.g. Belke, Brysbaert, Meyer, & Ghyselinck, 2005; Belke, 2008, 2013; for review, see Navarrete, Mahon, Lorenzoni, & Peressotti, 2016). The contrast between blocking effects in spoken picture naming and reading aloud has been used to localize the interference effect observed in spoken picture naming to semantically mediated lexical selection, since this is the key process that is necessary for picture naming but not for reading aloud.…”
Section: Semantic Similarity Effects In Spoken Productionmentioning
confidence: 85%
“…Therefore this task can be used to investigate the role of semantic similarity when lexical-syntactic information but not lexical-semantic information is necessary to complete the task. It contrasts with spoken picture naming, which requires lexical-semantic retrieval, and with reading aloud of bare nouns, which does not require either lexical-semantic or lexical-syntactic retrieval (e.g., Belke, 2013; Damian, Vigliocco, & Levelt, 2001; Navarrete, Mahon, & Caramazza, 2010; Navarrete et al, 2016). Results generally support the proposal that interference arises when lexical-syntactic information is necessary, although inconsistencies have been observed (for review, see Navarrete et al, 2016).…”
Section: Semantic Similarity Effects In Spoken Productionmentioning
confidence: 99%